National open university of Nigeria and promotion of digital education (2020)
This paper discusses the historical background us well us llie operations of the National Open University of Nigeria (NOUN) as the first federal University in Nigeria dedicated to the provision ofeducation through distance mode. Furthermore, the paper highlights the ways in which NOUN has promoted digital education to distance learning students. The challenges of e-learning in the operations ofthe University were examined, while recommendations were made an how it could enhance its delivery system for effective digital education